1999
DOI: 10.1590/s0100-879x1999001000006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and histopathological study of cyclophosphamide-induced hemorrhagic cystitis - comparison of the effects of dexamethasone and Mesna

Abstract: Chemotherapy with oxazaphosphorines, such as cyclophosphamide (CYP), is often limited by unacceptable urotoxicity. Without uroprotection, hemorrhagic cystitis (HC) becomes dose-limiting. To compare the uroprotective efficacy of classical 2-mercaptoethanesulfonic acid (Mesna) treatment with dexamethasone in CYP-induced HC, male Wistar rats (150-200 g; N = 6 in each group) were treated with saline or Mesna (40 mg/kg, ip) immediately and 4 and 8 h after ip administration of CYP (200 mg/kg). One, 2 or 3 doses of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…There is evidence that ACR reacts with mesna producing an inert thioether that is eliminated in the urine (19). Thus, in this model, as is also the case for humans or animals treated with oxazaphosphorine (20), mesna presented its uroprotective effect when administered systemically or locally.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…There is evidence that ACR reacts with mesna producing an inert thioether that is eliminated in the urine (19). Thus, in this model, as is also the case for humans or animals treated with oxazaphosphorine (20), mesna presented its uroprotective effect when administered systemically or locally.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, evidence also exists that ACR increases the release of IL-8 by neutrophils (26). In the present study, to validate the model of ACR-induced HC, the animals were treated with mesna, a classical uroprotector agent with established clinical (8) and experimental efficacy (20,27). The increase in BWW and Evans blue extravasation was blocked by pretreatment of the mice with mesna, regardless of local or systemic administration.…”
Section: Discussionmentioning
confidence: 74%
“…The bladders were removed and emptied of their urinary contents. The best time to access HC in rats is between 24 and 48 h according to the literature (Morais et al 1999), as shown by the increase in bladder wet weight (BWW) of rats. BWW drops signiWcantly after 48 h. Hence, we chose 24 h as the right time to access IFS-induced HC.…”
Section: Ifs-induced Hc Modelmentioning
confidence: 99%
“…CP is mainly used in the treatment of blood cancer, brain cancer, leukemia and some solid tumors (Pavan K. V., 2013 ). It is also used in the treatment of various nonneoplastic diseases like nephritic syndrome, systemic lupus erythematosus and rheumatoid arthritis (Morais et al, 1999). As CP is used to treat both neoplastic and non-neoplastic diseases, it is very important to assess the long-term carcinogenic potential of this drug (Travis et al, 1995).…”
Section: Cyclophosphamidementioning
confidence: 99%